Estudo da relação entre eficiência dos protocolos de desinfecção e contaminantes fúngicos no sistema dialítico - Lopes, Leonardo Guedes (2019)
The increase in demand for health services and the overload of chronic diseases in the population, especially chronic renal insufficiency (CRI), have contributed to higher rates of patients seeking hemodialysis as therapy, although risks of contamination microbiological are an adverse reaction to treatment. As a control measure, national legislation recommends disinfectants, concentration and exposure time in which they should be used for disinfection of the system, having as indicators of bacteria effectiveness. Thus, this study aimed to evaluate the efficacy of disinfectants used in the dialysis process in the face of fungi of the genus Aspergillus and Fusarium as well as in vivo toxicity, in order to reduce the risk of fungal infections and improve the quality of life of people undergoing dialysis treatment. Disinfectants were used: acetic acid, citric acid, peracetic acid, sodium hypochlorite and sodium metabisulfite, in the concentrations and exposure times recommended for hospital use, using fungal isolates of Aspergillus and Fusarium previously obtained from the water Circuit of hospital hemodialysis service. The lowest concentration of disinfectant that inhibiting the growth of free cells was determined by the broth dilution methodology, followed by plating on Agar, considering the effective concentration that reduced fungal growth in 99.9% (= 3 logUFC/ mL). For biofilms, the lowest inhibitory concentration was obtained by the Tetrazolium Salt reduction Method (XTT), with the effective concentration that reduced growth by 50% (measured in optical density – FROM 492 nm).The results showed that for the planctonic cells, for Aspergillus, sodium hypochlorite 2.5% and peracetic acid 0.1% were the most effective disinfectants while for Fusarium, sodium hypochlorite 2.5% and acetic acid 1%. For biofilms, Aspergillus was sensitive to sodium hypochlorite 2.5%, acetic acid 1%, citric acid 50% and sodium metabisulfite 0.1% while Fusarium showed similar results for the first three, but citric acid 50% showed to be more Efficient Metabisulfite 0.1% showed low efficiency for Fusarium biofimes.For the toxicity tests using the nematode C. elegans model, it was detected that the disinfectants sodium hypochlorite and peracetic acid, at the concentrations indicated for the process of disinfection of machines, were toxic to the larvae, since the Most of them died after exposure to them for 30 minutesIn the study of larval development, where the eggs were used, the resulted over doses showed that peracetic acid showed a lower degree of toxicity considering that in all concentrations tested (0.05%, 0.1% and 0.2%), the hatching of the eggs was obtained, Compared to those exposed to sodium hypochlorite, where only in one of the concentrations tested (0.025%) The hatch was obtained. In general, despite the lower toxic effect to the nematode, Peracetic acid 0.1%.Interfered in the larval development of the nematode. Thus, the study offers subsidies for the reassessment of the standardization of disinfection of the hemodialysis system, in order to provide greater safety and quality to users, an emerging population in the country before the aging population. Keywords: Disinfection, Hemodialysis, Quality of Life, Fungal Infection, C. elegans.